Metatheories of Indigenous Leadership: Modelling a Culturally Responsive Competency Theory - A Narrative Literature Review - Ferrol III, Tomas (JPAIR Institutional Research, 2026)
This narrative literature review synthesizes recent scholarship (2020-2025) to advance a culturally responsive leadership competency theory for Indigenous educational contexts. Drawing on propositions from Trait Theory, Organizational Behavior, Planned Change, and Cultural Leadership, the review integrates demographic traits, organizational development, policy adherence, motivation, and cultural competence into a unified framework. Findings indicate that educational attainment and linguistic competence serve as foundational predictors of leadership effectiveness, while organizational development mechanisms institutionalize competencies and sustain resilience. Policy adherence enhances trust and accountability, and motivation operates as a psychological driver of engagement. Cultural competence anchored in Indigenous values such as Pakikipagkapwa (shared identity), Bayanihan (collective effort), and Paglilingkod (service) moderates these pathways by embedding authenticity and cohesion into leadership practice. While existing studies often examine leadership traits, organizational processes, and cultural responsiveness in isolation, this review consolidates these previously fragmented strands into a single, integrative and culturally grounded competency framework. By doing so, it responds to calls in leadership and Indigenous education scholarship for models that bridge evidence based leadership theory and Indigenous epistemologies. Methodological advances, including Structural Equation Modeling and mixed-method designs, provide empirical rigor and contextual depth. Overall, leadership effectiveness emerges as a dynamic interplay of technical, relational, and cultural dimensions, interpreted through evidence-based and culturally grounded approaches.
Keywords: Indigenous leadership; culturally responsive leadership; organizational development; policy adherence; cultural competence; literature review